Calcular Los Integrales
Calcular Los Integrales
Calcular Los Integrales
X=1: 4A = 4 => A= -1
X=3: -8+6B+2C= 24 => 3B+C= 16 ----- I B= 12
X=2: -5+2B+C= -1 => 2B+C=4 ……….II C= -20
3x – 4 = A + Bx + C = A(x2+3x-1)+(Bx+c)(x-2)
(x-2)( x2+3x-1 ) (x-2) (x2+3x-1) (x-2)( x2+3x-1)
C)
x2 Dx = x2 _
4 2
(1-x ) (1-x)(1+x)(1+x )
D)
X Dx = X Dx = X Dx _
X6-1 3 3
(x +1)(x -1) 2 2
(x+1)(x-1)( x +x+1)(x -x+1)
C = -61 ; D = -65 ; E = -1 ; F = 65
198 198 6 198
1 + 1 - 61x + 65 - 33x – 65 Dx =
6(x+1) 6(x-1) 198(x2-x+1) 198(x2-x+1)
E) Dx =>
(x+1)2(x2+1)
A + B + Cx + D = A (X+1)2(X2+1)+B(X+1)(X2+1)+(CX+D)(X+1)3
(X+1) (X+1)2 X2+1 (X+1)2(X2+1)
(A+C)X4+)A+B+3C+D)X3+C2A+B+3C+3D)X2 + (2A+B+C+3D)X+A+B+D = 1
A+C= 0 A= 1 ; C= -1/3
A+B+3C+D= 0 3
2A+B+3C+3D=0 B= 7 ; D= -1/2
A+B+D=1 6
1 _ + 7 _ - 2X+3 Dx=
3(X+1) 6(x+1)2 6(x2+1)
1 Lm | X+1 | - 7 - 1 Lm | X | - 1 arcTgX + C
6 6( x+1) 6 2
A+C= 4 A= 0
2A+D+B= 4 B= 2
2A+2B= 4 C= 4
2B= 4 D= 2
x-2+ 2 + 4x+2 _ Dx = x2 + 2x – 2 + 2 Lm l x2 + 2x + 2 l - 2 arcTg(x+1) + C
x2 x2+2x+2 2 x
G) 3x2 + 3x + 1 Dx = 3x2 + 3x + 1 Dx
x3 + 2x2 + 2x 1 (x+1)(x2+x+1)
A+B = 3 A=1
A+B+C= 3 B=2
A+C= 1 C=0
1 + 2x _ Dx = Lm l X+1 l + Lm l x2 + x + 1 l – 2 arcTg 2x + 1 +C
X+1 x2 + x +1 √3 √3
H) 2x2 + x + 1 _ Dx =>
(X +3)(2x2 + x + 5)
2
2A+C= 0 A= 1
A+2B+D= 2 B= 2
5A+B+3C= 1 C= -2
5B+3D= 1 D= -3
X+2 - 2X + 3 Dx =
X2+3 2X2+X+5
I= 3 - 3 dx _
4(x2+x+3) 2 (x2+x+3)3
Aplicación en A:
A= 2X+1 + 3 DX , B = DX _
22(X2+X+3)2 11 (X2+X+3)2 (X2+X+3)2
B
APLICANDO EN B
B= 2X+1 + 2 DX ; D DX__
11(X2+X+3) 11 X2+X+3 X2+X+3
B) I = Dx = A + B + C + D Dx
2 2 2
(x-1) (x +x+1) x-1 (x-1) x +x+1 (x +x+1)2
2 2 2
SI X = 1 => B= 1/9
SI X = 0 => C+D= 8 +A
9
SI X = -1 => A= 4/3
SI X = 2 => C= 12 D= - 88
9
=> I = 4 DX + 1 DX + 12 DX - 88 DX _
3 X-1 9 (X-1)2 X2+X+1 9 (X2+X+1)2
A B
A= 5 DX = 5 ArcTg x-3
(x-3)2+4 2 2
B= 15(2X-6) DX + 13 DX _
(X2-6X+13)2 (X2-6X+13)2
D) I = X3 = AX+B + CX+D DX
(X +2X+2)2
2 2
(X +2X+2) (X2+2X+2)2
X3=AX3 + (2A+B)X2+(2X+2B+C)X+2B+D
A=1, B= -2 , C=2 , D=4
I= (X-2) DX + (2X+4) DX
X2+2X+2 (X2+2X+2)2
I= X + 3 DX _
4(X2+1)2 4 (X2+1)2
Dx = X + 1 Dx_
2 2 2
(X +1) 2(X +1) 2 X2+1
Dx = arcTg (X) + C
X2+1
I= DX = 15X5+40X3+33X + 15 ArcTgx + C
(x2+1)4 48(x2+1)3 48
(4X+1) DX = 1 + C1
2 2 2
(2X +X+1) (2X +X+1)
DX = 2 ArcTg 4X+1
2X2+X+1 7 √7